Handling Dangerous Goods Issues Based On Radio Frequency Identification as An Export-Import Solution - Nugraha, Adelio Shatara; Azisah , Nur (Maritime Park: Journal of Maritime Technology and Society, 2025)
Indonesia's maritime territory covers an area of 6,400,000 km², accounting for more than 77% of its total area, presenting significant prospects for maritime trade and economic growth through sea trade. With ports serving as important gateways for trade in goods, maritime transportation commands an 80% share of the global market. However, the handling of dangerous goods poses significant risks, requiring strict adherence to the International Maritime Dangerous Goods Code (IMDG Code) to ensure safety and compliance. Current challenges include inadequate regulations, non-compliance with Standard Operating Procedures (SOPs), and cases of document manipulation, which exacerbate safety concerns. This study proposes the utilization of Radio Frequency Identification (RFID) technology as a solution to enhance the process of identification, verification, and real-time monitoring of dangerous goods, thereby improving operational efficiency and accuracy. A Research and Development (R&D) method focused on potential problems identified through stakeholder interviews revealed common issues such as misclassification of goods and lack of transparency in documentation. The new RFID system features components such as tags, readers, and a management system that integrates live tracking and automatic classification verification. After conducting a pilot test, the system showed a 95% accuracy rate in item identification, which significantly reduced misclassification. The recommendations include phased implementation at key ports, cross-agency collaboration, comprehensive training for personnel, and future upgrades to RFID technology with Internet of Things (IoT) integration to further improve transparency and data security in dangerous goods logistics in Indonesia.